Evaluation of Urinary Purine Derivatives Creatinine Index as a Predictor of the Nutritional Status in Dairy Animals at Farm Level - Singh, V. K.; Singh, P.; Verma, A. K.; Mehra, U. R. (Indian Journal of Animal Nutrition, 2017)
A total of 120 farmers were selected as per stratified random design from eastern plain zone (UP-9) of Middle Gangetic Plains region to investigate the effectiveness of spot urine purine derivatives creatinine (PDC) index as a predictor of nutritional status of dairy animals at farm level. A bench mark survey was conducted to gather first hand information regarding the nutritional status of dairy animals (60 cattle and buffaloes each). It comprised data collection through questionnaire as well as collection of feed samples and spot urine samples. The data were again categorized into landless (n=24), marginal (n=24), small (n=24), medium (n=24) and large (n=24) farmer categories. The mean concentration of total purine derivatives (PD) in spot urine was higher in cattle than buffaloes ((14.08 vs. 3.20 mmol/L). The total PD level showed significant (P<0.05) differences in cattle belonging to medium and marginal farmers. However, total PD concentration in urine did not show any variation in buffaloes of different group of farmers. The PDC indices of cattle and buffaloes were comparable among farmers groups. The predicted and observed TDN intake was higher (P<0.05) in cattle of medium farmer than marginal farmers. The correlation between predicted and observed TDN deficit/excess was significant (P<0.05) in all the groups of farmers’ cattle except landless farmers’ cattle. In buffaloes, the predicted daily TDN intake did not show any significant variation, however, observed TDN intake showed significant (P<0.05) variation among buffaloes belonging to different groups of farmers. The predicted and observed TDN intake (deficit/excess) did not show any correlation among buffaloes of different farmers groups. Therefore, the PDC index in spot urine samples coul